Comparing Dung Beetle Species Assemblages Between Protected Areas and Adjacent Pasturelands in a Mediterranean Savanna Landscape (Rangeland Ecology & Management, 2012)
Dung beetles are considered keystone species because of their role in decomposition, seed dispersal, and control of vertebrate parasites in grazed habitats. Despite the ecological importance of this group to pasture ecosystem functioning, still little is known about its relationship with grazing management activities. We evaluated the conservation value of protected areas for dung beetle diversity by comparing two different management conditions of Mediterranean savanna in central Spain. Four different sites with wild herbivory (red deer, roe deer) were sampled inside the Cabañeros National Park, and four sites with traditional agrosilvopastoral management were sampled in a sheep farm near the park. The dung beetle species richness was similar between savanna conditions, but the total dung beetle abundance and biomass were considerably greater in the park grasslands than in the grasslands of the sheep farm. Dung beetle species composition, species dominance, and abundance by functional groups from both park and farm sites were different, despite the high similarity among the sampled sites in both hydric content and dung availability. Onthophagus maki (Illiger 1803) and O. furcatus (Fabricius 1781) were the dominant species in the park, while O. furcatus, Aphodius foetidus (Herbst 1783), and Caccobius schreberi L. were the dominant species on the farm. Species richness and abundance of telecoprids were higher in the park than on the farm. Abundance of paracoprids was also higher in the park than on the farm, while no differences in species richness and abundance of endocoprids were observed between both conditions. These results suggest that management activities such as plowing and the use of veterinary substances affect soil structure and dung quality and could be important factors that alter dung beetle assemblages in terms of composition, abundance, and biomass on traditional farms.